2006
DOI: 10.1107/s1600536806023130
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonding patterns in 2-amino-4,6-dimethoxypyrimidine–4-aminobenzoic acid (1/1)

Abstract: In the title cocrystal, C6H9N3O2·C7H7NO2, the 2-amino-4,6-dimethoxypyrimidine molecule interacts with the carboxyl group of the 4-aminobenzoic acid molecule through N—H...O and O—H...N hydrogen bonds, forming a cyclic hydrogen-bonded motif [R 2 2(8)]. This motif further self-organizes through N—H...O hydrogen bonds to generate an array of six hydrogen bonds with the rings having the graph-set notation R 2 3(6), R 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…Few of them are 2-amino-4,6-dimethoxy pyrimidine: 4-aminobenzoic acid (Thanigaimani et al, 2006), 2-amino-4,6-dimethoxypyrimidine: phthalic acid (Thanigaimani et al, 2007), 2-amino-4,6-dimethylpyrimidine: cinnamic acid (Balasubramani et al, 2005) and 2-amino-4,6-dimethylpyrimidine: 4-hydroxybenzoic acid (Balasubramani et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few of them are 2-amino-4,6-dimethoxy pyrimidine: 4-aminobenzoic acid (Thanigaimani et al, 2006), 2-amino-4,6-dimethoxypyrimidine: phthalic acid (Thanigaimani et al, 2007), 2-amino-4,6-dimethylpyrimidine: cinnamic acid (Balasubramani et al, 2005) and 2-amino-4,6-dimethylpyrimidine: 4-hydroxybenzoic acid (Balasubramani et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…For aminopyrimidine carboxylates, see: Chinnakali et al (1999); Lynch & Jones (2004); Stanley et al (2005). For aminopyrimidine and benzoic acid adducts, see: Balasubramani et al (2005Balasubramani et al ( , 2006; Thanigaimani et al (2006Thanigaimani et al ( , 2007. For hydrogen bonding in molecular recognition and crystal engineering, see: Desiraju (1989).…”
Section: Related Literaturementioning
confidence: 99%
“…For related literature, see: Baker & Santi (1965); Bernstein et al (1995); Chinnakali et al (1999); Etter (1990); Hunt et al (1980); Hunter (1994); Low et al (2002); Lynch & Jones (2004); Muthiah et al (2006); Schwalbe & Williams (1982); Thanigaimani et al (2006); Van Schalkwyk (1954). Symmetry codes: (i) Àx þ 2; y þ 1 2 ; Àz þ 1 2 ; (ii) Àx þ 2; y À 1 2 ; Àz þ 1 2 ; (iii) Àx þ 2; Ày; Àz.…”
Section: Related Literaturementioning
confidence: 99%
“…The crystal structures of aminopyrimidine derivatives (Schwalbe & Williams, 1982), aminopyrimidine carboxylates (Muthiah et al, 2006) and cocrystals (Chinnakali et al, 1999) have been reported. The crystal structure of 2-amino-4,6-dimethoxy pyrimidine (Low et al, 2002) and 2-amino-4,6-dimethoxypyrimidine-4-aminobenzoic acid (1/1) (Thanigaimani et al, 2006) have also been reported. The crystal structure of phthalic acid (Van Schalkwyk, 1954) is known.…”
Section: S1 Commentmentioning
confidence: 99%
“…For related literature, see: Baskar Raj et al (2003); Bernstein et al (1995); Lehn (1995); Panneerselvam et al (2002); Stanley et al (2005); Tavale & Pant (1971); Thanigaimani et al (2006). = 105.76 (3) V = 625.5 (4) Å 3 Z = 2 Cu K radiation = 1.08 mm À1 T = 293 K 0.26 Â 0.14 Â 0.13 mm…”
Section: Related Literaturementioning
confidence: 99%